An Analysis on the Students’ Indirect Learning Strategies in Writing Skill - Yusri Yusri; Tri Setiani (Universitas PGRI Palembang, 2018)
AbstractThe problem of this study was “what are the indirect learning strategies in writing skill applied by the eleventh grade students of State Senior High School 12 Palembang?” The objective of this study was to find out what the indirect learning strategies in writingskill are applied by the eleventh grade students of State Senior High School 12 Palembang. This study used qualitative descriptive method. The population of this study was 232 of the eleventh grade students of State Senior High School 12 Palembang in the academic year of 2016 / 2017. The class of XI IPA 1 that consisted of 38 students was chosen as the sample of this study. The data was collected through the SILL questionnaire and documentation. The data obtained was analyzed by using SPSS version 20. Based on the study, it showed that eventhough there was no learning strategy applied by the students in the high use, but according to the averageuse of the strategy, metacognitive strategies (Mean = 3.28) became the most frequently strategies applied by the students, then, followed by affective strategies (Mean = 2.65), and the last was social strategies (Mean = 2.46). In conclusion, all the indirect learning strategies in writing skill that are metacognitive, affective, and socialstrategies were applied by the eleventh grade students of State Senior High School 12 Palembang.Keywords: Analysis, Indirect Learning Strategies, and Writing Skill